2022
DOI: 10.3390/coatings12050664
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-Cut Mangoes: How to Increase Shelf Life by Using Neem Oil Edible Coating

Abstract: The mango is the most widely cultivated tropical fruit. Fresh-cut mango is very useful, but it is very perishable. The purpose of this study was to highlight the effects of neem oil on fresh-cut mango fruits kept for 9 days at 4 ± 1 °C and 80 ± 5% relative humidity. The neem plant (Azadirachta indica) has numerous antioxidant and antibacterial properties. Despite this, very few studies have been carried out on neem oil added to edible coatings (EC) to retard ripening processes. Two formulations were tested: EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Suriati ( 2021 ) and Passafiume et al. ( 2022 ) reported that coating applications reduce the loss of total soluble solids in fresh‐cut mangoes and help preserve the fruit's physicochemical properties. Passafiume et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suriati ( 2021 ) and Passafiume et al. ( 2022 ) reported that coating applications reduce the loss of total soluble solids in fresh‐cut mangoes and help preserve the fruit's physicochemical properties. Passafiume et al.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the concentration of total sugars in the fruits increases, contributing to elevated °Brix values (Riaz et al, 2021). Coatings play a crucial role in preserving the total soluble solids content by limiting the loss of fruit juice and maintaining the fruit's characteristics (Passafiume et al, 2022). Suriati (2021) and Passafiume et al (2022) reported that coating applications reduce the loss of total soluble solids in fresh-cut mangoes and help preserve the fruit's physicochemical properties.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…18 Neem oil is an essential oil obtained from the seeds of the neem plant (Azadirachta indica) and has been used for centuries due to its excellent antibacterial, antifungal, antioxidant and health-promoting properties. 19,20 However, its applications in food packaging and preservation are limited due to photosensitivity of neem oil and its impacts on the sensory attributes of food. To address these challenges, neem oil can be nano-emulsied to improve bioactivity, bioavailability, and photostability.…”
Section: Introductionmentioning
confidence: 99%
“…They can partially restrict the exchange of gas and vapor, which delays the shrinking of cut produce and modifies the environment around the good. Utilization of polysaccharide blend to minimize the undesirable changes due to several internal and external factors and minimal processing has been studied (Nicolau‐Lapeña et al, 2021 ; Passafiume et al, 2022 ; Shah & Hashmi, 2020 ; Tavassoli‐Kafrani et al, 2022 ). They have ability to prevent the fruits by improving the barrier, water vapor, and gas exchange properties.…”
Section: Introductionmentioning
confidence: 99%